Evaluation of breeding practices and morphological characterisation of donkeys in three selected villages of the Blouberg Local Municipality, in the Limpopo Province, South Africa - Maswana, Masixole (My University, 2022)
Donkeys continue to play a significant role in draught power activities for both rural and urban regions in underdeveloped countries, where they are commonly employed for transportation of goods and movement of people at extremely low prices. The study sought to determine donkey farmers' breeding practices as well as donkey morphological characterization in three villages such as Thorp, Archibalt and Genau of the Blouberg Local Municipality. A total of 21 donkey farmers and 74 donkeys were used to collect data. The following Morphological traits characterized were; Head length (HL), Ear length (EL), Neck length (NL), Chest width (CW), Back length (Bal), Body length (BoL), Hips width (HW), Umbilical circumference (UC), Back height (BH), Height at the rump (HR), Thoracic circumference (TC), Chest depth (CD), Withers Height (WH), Front leg length (FLL), Cannon circumference (CC), Cannon length (CL), Cannon height (CH) and Body weight (BW). Descriptive statistics, Chi-square tests, Analysis of variance (ANOVA), Pearson correlation, and Rank Index were used for data analysis. Education level of the farmers in the three villages was significantly different (p<0.05) with the majority of farmers having secondary education. There was no significant difference (p>0.05) amongst the villages on different reasons behind keeping donkeys. The results showed a significant difference (p<0.05) in inbreeding knowledge by the farmers amongst the three villages. The selection criteria used across the three villages were not significantly different (p>0.05). Rank and Indices in selection of male donkeys looked at body size (0.39), growth rate (0.19), Draught power performance (0.14), and for overall preference in female donkeys it was body size (0.26), twinning ability (0.23) and mothering ability (0.15). Body size and growth rate where the most important traits to donkey farmers. The coat colours were not significantly different (p>0.05). In all the eighteen measured traits, only four (BaL, HW, BH and FLL) showed a significant difference (p<0.05) among the three villages. BW in male donkeys was not significantly correlated (p>0.05) with HL, EL, NL, BaL, HW, FLL, CC, CH, CL but was positively correlated (p<0.05) with BoL (r = 0.34), UC (r = 0.35), TC (r = 0.33), CD (r = 0.31), CW (0.94), BH (r = 0.41), HR (0.60), and WH (r = 0.58). BW in female donkeys was not significantly correlated (p>0.05) with NL, BaL, TC, and CL but positively significant correlated (p<0.05) with HL, EL, BoL, HW, UC, FLL and CC CW, BH, HR, WH and CH with correlation coefficient values ranging from 0.34 to 0.75. The farmers had no breeding program in place the donkeys were allowed to mate on their own without designed breeding program. Selection of donkeys to be part of the heard was based on physical attributes, such length It was concluded that donkey farmers in Genau, Archibalt, and Thorp villages engaged in breeding practices that could be valuable in construction of a community-based breeding program.
Thesis(M.Sc. (Animal Production)) -- University of Limpopo, 2022
Keywords: Coat colour; Pearson's correlation; Preferred traits; Selection criteria; Inbreeding; Donkeys; Animal breeding; Donkeys -- Breeding; Donkeys; Farmers -- Social conditions